Enhanced transparent conducting networks on plastic substrates modified with highly oxidized graphene oxide nanosheets. Issue 12 (7th March 2016) - Woo, Jong Seok; Sin, Dong Hun; Kim, Haena; Jang, Jeong In; Kim, Ho Young; Lee, Geon-Woong; Cho, Kilwon; Park, Soo-Young; Han, Joong Tark
Abstract : Highly oxidized graphene oxide nanosheets serve as an effective interfacial modifier of transparent conducting films with one-dimensional conducting materials. Abstract : Atomically thin and two-dimensional graphene oxide (GO) is a very fascinating material because of its functional groups, high transparency, and solution processability. Here we show that highly oxidized GO (HOGO) nanosheets serve as an effective interfacial modifier of transparent conducting films with one-dimensional (1D) silver nanowires (AgNWs) and single-walled carbon nanotubes (SWCNTs). Optically transparent and small-sized GO nanosheets, with minimal sp 2 domains, were successfully fabricated by step-wise oxidation and exfoliation of graphite. We demonstrated that under-coated HOGO further decreases the sheet resistance of the SWCNT film top-coated with HOGO by increasing the contact area between the SWCNTs and HOGO nanosheets by generating hole carriers in the SWCNT as a result of charge transfer. Moreover, HOGO nanosheets with AgNWs contribute to the efficient thermal joining of AgNW networks on plastic substrates by limiting the thermal embedding of AgNWs into the plastic surface, resulting in efficient decrease of the sheet resistance. Furthermore, flexible organic photovoltaic cells with GO-modified AgNW anodes on a flexible substrate were successfully demonstrated.